Analisis Pengaruh Kesadaran Merek, Kredibilitas Endorser Selebriti, dan Mutu Produk terhadap Keputusan Pembelian Kosmetik Emina: Perspektif Konsumen Muda di Berau - Dewi Satriani; Heni Susilowati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of brand awareness, celebrity endorser, and product quality on the purchase decision of Emina cosmetic products among university students in Berau Regency, East Kalimantan. The background of this research is driven by the significant growth of the local cosmetic industry and the high adoption of Emina products among young consumers, especially students. As a popular local cosmetic brand, Emina has successfully captured the attention of its young audience with approaches that resonate with their characteristics. Therefore, it is important to understand the factors influencing their purchasing decisions. The study uses a quantitative approach with a survey technique involving 100 purposively selected respondents. Data was collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 25. The results of the study show that, simultaneously, all three independent variables (brand awareness, celebrity endorser, and product quality) significantly affect the purchase decision of Emina products. However, when analyzed separately, only celebrity endorser and product quality have a positive and significant influence, while brand awareness does not show a significant impact on the purchase decision. Product quality proves to have the most dominant influence in driving the purchase decision, indicating that consumers prioritize product quality over other factors. The findings provide important recommendations for marketing strategies, particularly for Emina, to focus on emotional value-based promotions that resonate with the young audience. In addition, the selection of relevant celebrity endorsers and consistency in maintaining product quality are crucial factors to consider. This research is expected to contribute to the development of evidence-based marketing strategies in the local cosmetic industry, particularly in non-metropolitan areas, which face unique challenges in increasing product adoption.